Hypotensive Peptides from Snake Venoms: Structure, Function and Mechanism - Xu, Xiaolong; Li, Bing; Zhu, Shanshan; Rong, Rui (Current Topics in Medicinal Chemistry, 2015)
Snake venoms have evolved over millions of years, and some toxins have evolved to specifically target various sites in the cardiovascular system of prey animals, producing prey hypotension. So far, a number of specific hypotensive peptides have been identified from different snake venoms. These snake hypotensive peptides are divided into five classes: bradykinin potentiating peptides, natriuretic peptides, sarafotoxins, Phospholipases A2 and L-type Ca2+ channel blockers. They differ widely in their structure, mechanism and points of action. Each class has many different isoforms with similar structures but different hypotensive activities. In the last decade, research efforts on snake hypotensive peptides have produced great advance in their understanding and applications in designing antihypertensive agents. In addition, several new classes of hypotensive peptides have been found from snake venoms. This review attempts to provide an overview of the current understanding of the structure, function and mechanism of snake hypotensive peptides.
Keywords: Snake venom